Menopausal hormone therapy at different stages of menopausal transition - Kokot-Kierepa, Marta; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Menopause is a natural stage of every woman’s life and therefore it is very important to create a positive attitude towards that transition time with its biological, psychological and social changes. Having in mind that the majority of women spend almost 1/3 of their life post menopause, assisting them in coping with menopausal transition becomes more and more important. This also includes the use of menopausal hormone therapy. An increasing body of conflicting evidence concerning HT demands reassessment of established paradigms of prevention of various diseases and menopausal health. Different combinations of different hormones in appropriate doses are required for the treatment of various symptoms and different age groups. Special emphasis should be placed on the time of HT initiation – starting in the so-called “window of opportunity” (45-60 year old symptomatic women) might be the most beneficial for the patient. Clinicians need to estimate individual benefit-risk ratios of HT for every patient treated, taking into account the complex nature of oestrogen’s actions on almost every organ system.